2011
DOI: 10.1146/annurev-fluid-122109-160718
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Methods for High-Speed Flows

Abstract: We review numerical methods for direct numerical simulation (DNS) and large-eddy simulation (LES) of turbulent compressible flow in the presence of shock waves. Ideal numerical methods should be accurate and free from numerical dissipation in smooth parts of the flow, and at the same time they must robustly capture shock waves without significant Gibbs ringing, which may lead to nonlinear instability. Adapting to these conflicting goals leads to the design of strongly nonlinear numerical schemes that depend on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
219
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 399 publications
(221 citation statements)
references
References 137 publications
1
219
0
1
Order By: Relevance
“…The flow solver relies on central sixth-order discretization of the convective terms of the Navier-Stokes equations cast in fully split form (Pirozzoli 2011), which guarantees discrete conservation of the total kinetic energy in the limit case of inviscid, incompressible flow, also in the presence of grid stretching in the coordinate directions. This approach allows robust spatial discretization of the convective terms without the addition of any spurious numerical dissipation in the form of upwinding or filtering.…”
Section: Computational Setupmentioning
confidence: 99%
“…The flow solver relies on central sixth-order discretization of the convective terms of the Navier-Stokes equations cast in fully split form (Pirozzoli 2011), which guarantees discrete conservation of the total kinetic energy in the limit case of inviscid, incompressible flow, also in the presence of grid stretching in the coordinate directions. This approach allows robust spatial discretization of the convective terms without the addition of any spurious numerical dissipation in the form of upwinding or filtering.…”
Section: Computational Setupmentioning
confidence: 99%
“…Especially, some low dissipative WENO type schemes have been proposed, such as compact-WENO [11,12], WENO-Z [13], WENO-SYMBO [14], TWENO [15], which have been successfully used for multi-scales capture. As Pirozzoli [16] reviewed and suggested that the hybridization of a high-order compact scheme with the WENO scheme is good choice for the DNS and larger eddy simulation (LES) of turbulent compressible flows. Moreover, it is still an arduous work to enhance the robust or stability of such low dissipative and high resolutive methods, especially for the case of flow with high Mach number or high Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…However, unless otherwise noted, all central difference results reported in this paper use the Kennedy and Gruber flux in Eq. (14). The flux values for G i,j+ 1 2 ,k and H i,j,k+ 1 2 , formed at the half-nodes in the j-and k-direction respectively, are formed in the same way.…”
Section: Methodsmentioning
confidence: 99%